Work with video display terminals among office employees. I. Subjective symptoms and discomfort. - Knave, B. G.; Wibom, R. I.; Voss, Margaretha; Hedstrom, L. D.; Bergqvist, U. O. (Scandinavian Journal of Work, Environment & Health, 1985)
Subjective symptoms and discomfort were evaluated by means of a questionnaire and compared between approximately 400 video display terminal (VDT) operators and 150 selected referents. Previous and current illnesses, educational status, and smoking and drinking habits were also studied. The results showed the VDT operators to have more eye discomfort and possibly also more musculoskeletal discomfort in the shoulders, neck, and back than the referents. The VDT group also reported more skin disorders. In addition, women reported consistently more disorders than men, regardless of whether or not they were employed in VDT work. Women in general displayed greater morbidity than men. Eye discomfort, musculoskeletal discomfort, headache, and skin disorders were found to be significantly correlated in the material. The results also indicated that total daily workhours and time spent looking at the VDT screen were related to the degree of discomfort. Even when the subjects were divided into subgroups with reference to the various enterprises, the types of work and the makes of VDT, the differences obtained in the degree of discomfort appeared to be due to variations in the length of workhours.